Implementation of Yin Algorithm to Detect Human Voice Emotions According to Gender: Implementation of Yin Algorithm to Detect Human Voice Emotions According to Gender - Aulia, Fikri; Basuki, Achmad; Dewantara, Bima Sena Bayu (Jurnal Mantik, 2020)
Computer technology and artificial intelligence experience rapid development every year, one of which is in media speech recognition. Speech recognition is a virtual digital data assistant that exists in software applications, and is used as a tool to help human needs such as communication, but is often misused by users. This study conducted a voice recording to get the difference in the sound of each human gender data. The study uses the Yin algorithm to extract data, then the sound pitching process is performed using the histogram pitch feature of the standard deviation and the mean. From this study, it was found that the pitch of men is different from women. The shape of the pitch histogram contours is similar between men and women but the female pitch histogram shifts to a higher frequency than men. This pitch shift in women occurs in all expressions.